PENGARUH PENGGUNAAN METODE JOLLY PONICS DENGAN MODEL KOPERATIF TERHADAP KEMAMPUAN MEMBACA PADA SISWA KELAS II SD NEGERI 101931 PERBAUNGAN - Nursila , Nursila; Safrida Napitupulu (Jurnal Cakrawala Ilmiah, 2025)
The Jolly Phonics method is a way of teaching reading by using letter sound synthesis to read words and teaching the sounds of letters in a multisensory manner. Learning to read at an early stage using a phonics approach is a very good first step for children. Children who hear a variety of sounds in words and who are able to use the sounds in words are more successful in learning to read. This research aims to analyze the effect of using the Jolly Ponics method with a cooperative model on the reading ability of class II students at SD Negeri 101931 Perbaungan. The research uses quantitative research. This study used research instruments in the form of a pretest and posttest to test the effect of using the jolly ponics method with a cooperative model on reading ability in class II students at SD Negeri 101931 Perbaungan. Based on the research results and discussions that have been found, the researcher can draw the conclusion that the simple linear regression equation from this research is: Y = 11.575 + 0.414X. The constant value (a) is 11.575. This means that if the Jolly Ponics Method variable (X) has a value of 0, then the value is positive, namely 11,575. The regression coefficient value for the Jolly Ponics Method variable (X) is positive, namely 0.414. This means that if there is an increase in the Jolly Ponics Method (X) by 1%, then students' reading ability will increase by 0.414 assuming other variables are constant. There is a positive influence between the jolly ponics method on the reading ability of class II students at SD Negeri 101931 Perbaungan, this is proven by the t-count value of the jolly ponics method variable of 2.358